PENGARUH INTERAKSI ANTAR NEGARA ASEAN DALAM PENGAMBILAN KEBIJAKAN DI ERA TEKNOLOGI INFORMASI - Astika, I Putu (Jurnal Diplomasi Pertahanan, 2020)
Current global and regional conditions have an influence on policies so that in conducting interactions between countries, they will relate to the surrounding countries. Countries in the Southeast Asian region as in ASEAN have the same foundation in achieving their national interests so that it will affect the interactions that occur in this era of information technology. This aim is not solely done to create mutual trust, but to prevent conflicts and disputes. The development of information technology will certainly affect state interactions so that the state in achieving its interests must be based on existing interactions. Countries in ASEAN have relationships and interactions that exist within them, be it in the economic, social, cultural, educational and even political fields. The purpose of this research is to study, know and analyze the influence of interaction between ASEAN countries in the Information Technology Age. This research method uses qualitative research methods with descriptive analytical research type so that the authors participate in analyzing the problems that occur. The results of this study indicate that there is an influence of interaction that exists between ASEAN countries in the Information Technology Age so that in achieving their interests, ASEAN countries interact in these various fields.